The Criticality of Foreign Direct Investment on Financial Development: A Case Study of Pakistan - Batool, Aliza; Khan , Qasim Raza; Akram, Maria; Tariq , Adnan Bin; Qamri, Ghulam Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
Economic growth and financial development are fueled by foreign direct investment. It is curial for emerging markets and developing economies. The relationship between foreign direct investment (FDI) and financial development (FD) in Pakistan between 2001 and 2020 is empirically surveyed in this study. We have taken the Financial development (domestic credit to private sector % of GDP) as our dependent variable while FDI, (net inflows % of GDP), trade openness (TO), population growth (PG) and inflation (INF) as our independent variables. We extracted our all data of our variables from World Bank (WDI). Augmented Ducky fuller (ADF) and Philips Peron (PP) has been used to check the stationarity of data before using ARDL. Furthermore; we have applied Long Run Bound Test in order to know the long run relation. The findings indicate that foreign direct investment (FDI) and population growth (PG) have positively impact on financial development (FD). Additionally, the study finds that, in the case of Pakistan, trade openness (TO) is insignificant to financial development whereas inflation (INF) have a negatively significant. We applied Cusum and Cusum square test for model stability. The results of stability test show that our model is stable as are plots are within the critical bound. The study will help to design such policy that will attain specific goals to enhance foreign direct investment and financial development. It is anticipated that the findings would provide empirical insights and practical consequences for scholars and policy makers.